2017
DOI: 10.1590/1678-992x-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerin in anaerobic co-digestion of dairy cattle manure increases methane production

Abstract: Anaerobic digestion of crude glycerin (CG) along with animal waste has been an excellent option for increasing the production of biogas and methane to achieve efficiency in the treatment of both residues. This study aimed to evaluate improvements in specific productions of biogas and methane, reductions in solid and fibrous components in substrates prepared with dairy cattle manure and CG (containing 14 % glycerol). With these residues, experimental substrates were prepared and placed in 25 batch digesters. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…were added, which matches YAMASHIRO et al (2013) andSIMM et al (2017). Those studies reported, respectively, 254.6L biogas.kg VS -1 and 250L biogas.kg TS added -1 during the co-digestion of cattle manure and residues with high lipid content.…”
Section: Specific Biogas Yieldmentioning
confidence: 53%
See 1 more Smart Citation
“…were added, which matches YAMASHIRO et al (2013) andSIMM et al (2017). Those studies reported, respectively, 254.6L biogas.kg VS -1 and 250L biogas.kg TS added -1 during the co-digestion of cattle manure and residues with high lipid content.…”
Section: Specific Biogas Yieldmentioning
confidence: 53%
“…Anaerobic biodigestion by itself adds value to animal manure due to the benefits of energy recycling, as pointed out in studies that reported yields of up to 238L biogas.kg volatile solids (VS) -1 for swine manure and 250 L biogas.kg VS -1 for cattle manure (SIMM et al, 2017). Such high biogas yields could be further potentialized since the process is impacted by Sunada et al nutrient availability in the fermentation substrate.…”
Section: Introductionmentioning
confidence: 99%